Vulvar Hemangioma: Case Report - Janine Medeiros da Silva; Emily Ramos Calife; João Victor de Sousa Cabral; Hildemárzio Pinheiro Falcão de Andrade; Ana Katherine Gonçalves (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Hemangioma is a benign neoplasm that may affect the vulva, and it can cause functional or emotional disability. This article reports the case of a 52-year-old female patient with a history of a genital ulcer for the past 3 years and who had undergone various treatments with creams and ointments. The patient was biopsied and diagnosed with vulvar hemangioma and was subsequently submitted to surgical excision of the lesion. We emphasize the importance of following the steps of the differential diagnosis and proceeding with a surgical approach only if necessary.